PENGELOLAAN GEOWISATA BERKELANJUTAN DALAM MENDUKUNG PELESTARIAN WARISAN GEOLOGI: PERSPEKTIF COLLABORATIVE GOVERNANCE - Mahardhika Berliandaldo; Angga Wijaya Holman Fasa (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
Tourism trends after the Covid-19 pandemic show a tendency to outdoor nature tourism to avoid transmission of the virus. One of these types is geotourism. This study aims to identify and understand the urgency of sustainable geotourism management in supporting the preservation of geological heritage, as well as the roles and relationships between stakeholders in sustainable geotourism management in supporting the preservation of geological heritage based on a collaborative governance perspective. After obtaining the findings of the study on these two issues, a sustainable geotourism management strategy was developed to support the preservation of geological heritage based on collaboration between stakeholders. To elaborates these issues, a qualitative method with an analytical descriptive approach was applied. Based on further elaboration, this study shows several things, first, the management and utilization of this geological heritage can increase state revenues from the tourism sector with local economic and cultural development, as well as the harmony of spatial planning in an effort to realize sustainable development. Second, the role and relationship between stakeholders is needed in a collaborative framework that needs to be supported by a clear institutional system in order to manage finances and income, facility management, resolve technical problems, take care of daily management systems, regulation of collaboration of actors such as local businesses, academics, entrepreneurs, local governments, tourism agencies and local communities. Third, the strategy for sharing roles in the development of geotourism is by applying the pentahelix model which involves several stakeholders, including the Academy (Research and Community Services), Business (Cooperation in Financing and Business Organizers), Community (Supporting Tourism and Creative Economy), Government ( Coordinator and Regulator), Media (Promotion, Marketing, and Socialization).